The bioregionalisation revival - Ebach, Malte C. (Zootaxa, 2013)
The aim of this paper is to review some of the economic drivers of large scale bioregionalisation, using examples from deep sea hydrothermal vent communities, the Antarctic and sub-Antarctic, andAustralia. These economic drivers are mainly recent conservation efforts, while early 20th century bioregionalisation was driven by 19th century taxonomy and exploration to assess available biological resources for economic exploitation. Modern regionalisation, particularly of the Antarctic and deep sea hydrothermal vent communities, are driven by conservation studies to protect areas from economic exploitation, rather than biogeographical questions concerning endemism and natural classification.